1993
DOI: 10.1007/bf00040111
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of embryogenic cell suspension cultures from immature and mature embryos of barley (Hordeum vulgare L.)

Abstract: Two finely-dispersed, homogeneous and regenerable cell suspension cultures were established from embryogenic callus derived from immature and mature embryos in barley. The quality and viability of suspension cells obtained were determined using differential-interference-contrast microscope and fluorescence microscope. Cell suspension cultures, maintained in modified liquid CC medium, showed a 10-fold increase in dry weight after two weeks with a doubling time of about 3 days. Addition of L-proline and casein h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Eight of 30 initiated suspensions in AA medium, and four of 30 suspensions in mMS medium were established in our experiment. Weekly changes of medium, which maintained the suspensions in exponential growth, were in agreement with previous results mentioned for rice ), wheat (Vasil et al 1990) and barley (Huang et al 1993).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Eight of 30 initiated suspensions in AA medium, and four of 30 suspensions in mMS medium were established in our experiment. Weekly changes of medium, which maintained the suspensions in exponential growth, were in agreement with previous results mentioned for rice ), wheat (Vasil et al 1990) and barley (Huang et al 1993).…”
Section: Discussionsupporting
confidence: 86%
“…It was found that the two steps used for rice (Jenes and Pauk 1989), wheat (Harris et al 1988;Wang et al 1990) and barley (Huang et al 1993) were necessary for plant regeneration of rye. In the first step, protocalli were transferred to mMS growth medium (supplemented with 0.5 mg l -1 2,4-D) for compact embryogenic calli development.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, Singh (1986) and Gaponenko et al (1988) observed that diploid cells predominated in morphogenic calli obtained from immature barley embryo while polyploid and aneuploid cells increased significantly or even predominated when calli became non-morphogenic. A correlation between chromosomal variability and morphogenic capability in barley embryogenic suspensions (Huang et al, 1993) has also been indicated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the addition of activated charcoal [1,25,24,16], inclusion of different concentration of L-proline in the culture medium [5,4,9,19,7] and cold pretreatment of whole buds or anthers [12] or different concentrations of NAA and BA combination [20,21,18] could increase embryo production. Beneficial effects of temperature shock treatments on anther culture productivity were known.…”
Section: Introductionmentioning
confidence: 99%